2006
DOI: 10.1002/jor.20101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TGF‐β inducible early gene deficiency on flexor tendon healing

Abstract: The role of transforming growth factor b (TGF-b) in tendon healing is still not clearly established. TGF-b affects gene expression primarily through the activation of the Smad signaling pathway. The first step in the Smad pathway is the expression of TGF-b inducible early gene (TIEG). Recently, a TIEG knockout mouse has been developed. The purpose of this study was to examine the healing potential of flexor tendons in mice lacking the TIEG gene, and to further examine what role the TIEG pathway plays in flexor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 33 publications
1
33
0
1
Order By: Relevance
“…Tensile force-mediated upregulation of the ␣1 procollagen gene (Col1a1) was found to depend on the release of transforming growth factor-␤ (17). In the present study, gene expression changes in Tieg1 after leptin treatment supports the role of a transforming growth factor-␤-dependent signal pathway in this remodeling process (22,52). Our study also found increased expression levels of the Stat1 gene after leptin treatment, suggesting that direct activation of the JAK-STAT signaling pathway mediated through leptin receptors may be important (9,13,48).…”
Section: Discussionsupporting
confidence: 59%
“…Tensile force-mediated upregulation of the ␣1 procollagen gene (Col1a1) was found to depend on the release of transforming growth factor-␤ (17). In the present study, gene expression changes in Tieg1 after leptin treatment supports the role of a transforming growth factor-␤-dependent signal pathway in this remodeling process (22,52). Our study also found increased expression levels of the Stat1 gene after leptin treatment, suggesting that direct activation of the JAK-STAT signaling pathway mediated through leptin receptors may be important (9,13,48).…”
Section: Discussionsupporting
confidence: 59%
“…Subsequent studies from the laboratory or Dr. Thomas Spelsberg have revealed an important role for this factor in the regulation of bone mineralization [56], osteoclast differentiation [56] and epithelial proliferation [57,58]. KLF10 can modulate Smad signaling in osteoblasts and mice with systemic KLF10 deficiency are osteopenic [59] and have impaired tendon healing in response to mechanical injury [60].…”
Section: Klf10mentioning
confidence: 99%
“…The aforementioned results may be due to KLF10 transcription being induced by factors other than TGF-β, including estrogen and epidermal growth factor (8,14,30,31). Furthermore, certain intracellular proteins, including KLF11, were recently reported to exhibit effects similar to those of KLF10 (26,32).…”
Section: Discussionmentioning
confidence: 99%